Explicit instructional moves in teaching reading in grade one: Observations from four Amharic classrooms - Nigist Gedife Hunegnaw; Elena Tkachenko; Emilia Andersson-Bakken (College of education, Bahir Dar University, 2024)
In response to the recurring poor literacy achievement among learners in various mother tongue languages in Ethiopian schools, this study investigated teaching practices of four Amharic teachers at three government schools in Hawassa city, focusing on how the instructional content is implemented and what explicit instructional moves the teachers used in teaching early reading. Through a qualitative case study approach, utilizing video-recordings and checklist-based observations as data collection tools, the study revealed variations in implementation among all four teachers. Modelling, discussion, feedback and guided practice have been found to be the explicit instructional moves most prominently used by the teachers. Elements of explicit instruction seemed to be implemented simultaneously, albeit randomly, and the lesson content was delivered systematically from simple to more complex. The instructional content was found to be primarily grapho-phonological, where the fidäl was the minimal content unit of the instruction. Finally, the findings indicate that teaching practices are influenced by external factors such as lack of literacy materials and inadequate Amharic language competence among some teachers. The results might suggest the need for future policy changes and practical interventions aimed at enhancing teachers' competence and improving the provision of adequate literacy instructional materials.